PERLINDUNGAN HUKUM TERHADAP KONSUMEN PENGGUNA OBAT PELANGSING “RD PELANGSING” TANPA IZIN EDAR (Studi Putusan Nomor: 142/Pid.Sus/2020/Pn.Ktn) - Sabrina Sana’a Husna; Jeane Neltje Saly (Jurnal Hukum Adigama, 2021)
Southeast Aceh Regency is famous for many cases of selling Slimming Drugs without a distribution permit and prohibited from being circulated by BPOM. One of them is RD Slimming Drugs. RD Slimming drug is famous for losing weight fast, 1 bottle contains 30 capsules. People who are interested in slimming drugs are very much able to lose weight quickly without having to be tired, difficult and tired. The RD Slimming drug is proven to contain sibutramine, where the sibutramine content in the slimming drug is considered dangerous and has side effects. Where should slimming drugs only contain herbal ingredients that are harmless and safe for consumption. The problem in this study is that business actors do not include information about the composition of the slimming drug content, side effects of the drug in the packaging label and description of the drug. RD Slimming drugs are also not registered with BPOM but are still traded by business actors against the provisions of the Act. The purpose of this study was to determine the form of legal protection for consumers who use RD Slimming drugs without a distribution permit in Aceh. This research uses a descriptive normative juridical method. The data sources used are primary, secondary, and tertiary data. The results of this study indicate that business actors know that the RD Slimming Drug does not have a distribution permit but is still circulated and does not include the composition and side effects on the packaging label. In conclusion, consumers are harmed by business actors who deliberately trade and sell RD Slimming Drugs without a Marketing Permit so that it has a bad impact on consumer health.